Reform and Change in Higher Education
XVI, 363 p.
Keywords: Starting from the now classical book by Ladislav Cerych and Paul Sabatier (1986), the editors present a critical appreciation of that initial work and a review and critical appraisal of current empirical policy research in higher education. In the second part, a set of chapters analyses the effective and specific complexities of the implementation of higher education policies in several countries, offering a wide variety of situations both in terms of duration of implementation, legal objectives, adequacy of causal theories underlying the reforms, adequacy of financial resources and degree of commitment of the main actors of the process. Some of these chapters use alternative theoretical frameworks developed since the 1986 Cerych and Sabatier theorization to interpret the empirical results, and some national cases do not fall within the scope of Cerych and Sabatier’s analysis. The national case studies are: Australia (2), Austria, Finland, Italy, Mexico, The Netherlands, Norway, Portugal, Spain, South Africa, Sweden, the UK and the USA.